Peran Kurikulum dalam Perencanaan Pendidikan di Taman Kanak-kanak: Tantangan dan Peluang - Devi, Ulma; Ilmi, Darul; Junaidi, Junaidi; Jannah, Nadyya Zahratul; Yunita, Irma (BUHUTS AL ATHFAL: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This study aims to describe the role of the curriculum in planning early childhood education by analyzing the challenges and opportunities. Done by using library research methods. This research resulted in a number of challenges in curriculum planning and development, namely individual diversity, limited resources, lack of understanding of early childhood education, changes in societal demands and expectations. As well as opportunities including: child-based approaches, the use of educational technology, parent and community collaboration, research and innovation. Thus the curriculum and educational planning have a role in responding to all challenges by taking advantage of the opportunities that exist.